The geographic and phylogenetic structure of public DNA barcode databases: an assessment using Chrysomelidae (leaf beetles) - Lo, Ellie; Nie, Rui-E; Vogler, Alfried P. (Frontiers in Ecology and Evolution, 2024)
Introduction DNA barcoding in insects has progressed rapidly, with the ultimate goal of a complete inventory of the world’s species. However, the barcoding effort to date has been driven by a few national campaigns and leaves much of the world unsampled. This study investigates to what degree the current barcode data cover the species diversity across the globe, using the leaf beetle family Chrysomelidae as an example. Methods A recent version (June 2023) of the Barcode-of-Life database was subjected to test of sampling completeness using the barcode-to-BIN ratio and sampling coverage (SC) metric. All barcodes were placed in a phylogenetic tree of 600 mitochondrial genomes, applying phylogenetic diversity (PD) and metrics of community phylogenetics to national barcode sets to test for sampling completeness at clade level and reveal the global structure of species diversity. Results The database included 73342 barcodes, grouped into 5310 BINs (species proxies) from 101 countries. Costa Rica contributed nearly half of all barcode sequences, while nearly 50 countries were represented by less than ten barcodes. Only five countries, Costa Rica, Canada, South Africa, Germany, and Spain, had a high sampling completeness, although collectively the barcode database covers most major taxonomic and biogeographically confined lineages. PD showed moderate saturation as more species diversity is added in a country, and community phylogenetics indicated clustering of national faunas. However, at the species level the inventory remained incomplete even in the most intensely sampled countries, and the sampling was insufficient for assessment of global species richness patterns. Discussion The sequence-based inventory in Chrysomelidae needs to be greatly expanded to include more areas and deeper local sampling before reaching a knowledge base similar to the existing Linnaean taxonomy. However, placing the barcodes into a backbone phylogenetic tree from mitochondrial genomes, a taxonomically and biogeographically highly structured pattern of global diversity emerges into which all species can be integrated via their barcodes.